Assistance in Digital-Based Health Economic Management to Improve Cost Efficiency of Herbal MSMEs in Kediri City - Titin Susanti; Syahril Wahyu Ramadhan (Universitas STRADA Indonesia, 2026)
Herbal MSMEs play a vital role in supporting the public health economy, but they still face challenges in managing their businesses, particularly in financial recording and operational cost efficiency, due to low digital literacy in optimally utilizing technology. This community service activity focuses on digital-based health economic management mentoring, aimed at improving skills in digitalized financial recording. Mentoring was conducted on three MSMEs in Kediri City out of fifteen that have been operating for the past five years. The pretest-posttest method, comparing the percentage values ​​before and after mentoring through questionnaires, interviews, and observations, concluded that there was an increase in digital financial literacy, business cost control, and data-based economic decision-making. This mentoring has an impact on increasing the operational cost efficiency of herbal MSMEs without compromising product quality and is an effective strategy in strengthening the independence and sustainability of herbal MSMEs.